The Economic Burden of the COVID-19 Pandemic in State of Kuwait - Nur AM; Aljunid SM; Almari M (Dove Medical Press, 2024)
Amrizal Muhammad Nur,1 Syed Mohamed Aljunid,2 Mohammad Almari1 1Department of Health Policy and Management, College of Public Health, Health Sciences Center, Kuwait University, Shadadiya, Kuwait; 2Department of Public Health and Community Medicine, International Medical University, Kuala Lumpur, MalaysiaCorrespondence: Amrizal Muhammad Nur, Department of Health Policy and Management, College of Public Health, Health Sciences Center, Kuwait University, Shadadiya, Kuwait, Tel +965-55186373, Fax +965-24633632, Email amrizal65@gmail.comPurpose: The main aim of this study is to estimate the provider's cost, patients' cost (home and institutional quarantine cost) and the total economic burden of COVID-19 for patients with PCR positive in Kuwait.Patients and Methods: This cross-sectional and retrospective study identified the cost incurred for treating COVID-19 inpatients admitted to a General Hospital in Kuwait, a designated COVID-19 treatment center by the Kuwait Government during pandemic. A total of 485 COVID-19 patients were randomly selected from May 1st to September 31st, 2021. Data on sociodemographic information, length of stay (LOS), discharge status, and comorbidities were obtained from the patients' medical records. A step-down approach was done to estimate the healthcare provider cost per patient per admission. Patient cost (loss of productivity due to hospitalization, institutional and home quarantine) was calculated using human capital approach. The national economic burden of COVID-19 was estimated using costing data from a general hospital for the entire nation. The data were analyzed using the statistical software package SPSS version 25.Results: In all, 485 COVID-19 patients were involved in the research. KD 2216 (USD 7,344) was the average cost per patient per admission. The ICU accounted for 20.6% of the total cost, the physician and nursing staff for 42.1%, and the laboratory services for 10.2%. The estimated annual cost of care for COVID-19 patients in Kuwait was KD 147.4 (USD 488.5) million, or 5.5% of the MOH budget for 2021, given that 9.03% (383,731) of the population had positive COVID-19 PCR results in 2021. The range of the estimated national economic burden, considering both the best and worst-case scenarios, is KD 73.6 (USD 244.2) million to KD 221.0 (USD 732.7) million.Conclusion: COVID-19 poses a substantial financial strain on the healthcare system, estimated at 5.9% to 8.8% of the MOH's annual budget and 0.2% to 0.7% of Kuwait's GDP in 2021. To mitigate costs, prioritizing prevention and health education is crucial. Targeted strategies, such as workforce optimization, are needed to address high expenses. Policymakers and administrators should leverage these insights for enhanced efficiency and sustainability in future epidemic responses.Keywords: COVID-19, coronavirus, economic burden, provider costs, patient cost